Faktor Yang Mempengaruhi Perkembangan - Isnadiatul Husna; Indah Jumadila Khairani; Liyoni Janika; Linda Yarni (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Psychology is a field that investigates thoughts, behavior and mental processes in humans. Over the years, this field has experienced many changes and developments influenced by various factors, including history, culture, religion, and social context. These factors also play an important role in shaping Western and Islamic psychological perspectives. In this article, we will further explore the factors that influence the development of these two perspectives.